Language Learning Strategies Used by the Students and Their Achievement in English Subject (a Case Study of Students Who Possess Kartu Jakarta Pintar at SMK Jakarta Pusat I) - R Sri Ayu Indrapuri (Wahana Didaktika : Jurnal Ilmu Kependidikan, 2023)
This research was intended to know the learning strategies used by students who possess Kartu Jakarta Pintar in English at SMK Jakarta Pusat I. This research aims to investigate the kind of language learning strategies frequently used by the students who possess KJP in SMK Jakarta Pusat 1. This was a qualitative research that kind of case study research. This study's respondents were the SMK Jakarta Pusat 1 student on April 2023. The population of this research was all the students who get Kartu Jakarta Pintar at SMK Jakarta Pusat 1 of the three classes, the total was 51 students. The respondents were given the questionnaire to be answered. In analyzing the result of the questionnaire, the writer uses Oxford’s SILL Profile of Result (Ver. 7). The learning strategy frequently used by students who possess KJP is metacognitive strategy. It shows 66% or 34 students out of 51 students. Learning strategy that is mostly used by the high achievement students who possess KJP is metacognitive strategy. It shown 50% of the students mostly use Metacognitive strategy. Learning strategy that is mostly used by the Low achievement students who possess KJP is social strategy. It shows 50% of the students mostly use Social strategy. Therefore, the three conclusions above have answered the objective of the research that the kind of learning strategy frequently used by students who possess KJP is metacognitive strategy.